Protection of the Witnesses and Victims: International Legal Acts, Legislation of some States and the Modern Russian Legislation - MAKEEVA, Inna V.; TASAKOV, Sergei V.; MISHIN, Andrei V.; SLED, Yurii G.; EPIKHIN, Alexander Y.; ZEINALOVA, Larisa M. (Journal of Advanced Research in Law and Economics, 2016)
The article represents a comparative analysis of a number of international acts (Conventions, Charts, and Guidelines) and legislations of several states including Kazakhstan, Belarus, Ukraine, Latvia concerning protection of the witnesses, the victims and some other individuals involved in criminal proceedings. Besides, the article reveals that development of norms of the international law makes positive impact on the national Russian legislation and defines main tendencies of convergence of international legal norms into the Russian legal framework. The Russian lawmaker has lately adopted a number of significant laws, subordinate and some other legal acts ensuring the witness protection and security as well as sufficient federal financial support of the public protection measures.